Key virulence factors responsible for differences in pathogenicity between clinically proven live-attenuated Japanese encephalitis vaccine SA14-14-2 and its pre-attenuated highly virulent parent SA14. - Byung-Hak Song; Sang-Im Yun; Joseph L Goldhardt; Jiyoun Kim; Young-Min Lee (PLoS Pathogens)
Japanese encephalitis virus (JEV), a neuroinvasive and neurovirulent orthoflavivirus, can be prevented in humans with the SA14-14-2 vaccine, a live-attenuated version derived from the wild-type SA14 strain. To determine the viral factors responsible for the differences in pathogenicity between SA14 and SA14-14-2, we initially established a reverse genetics system that includes a pair of full-length infectious cDNAs for both strains. Using this cDNA pair, we then systematically exchanged genomic regions between SA14 and SA14-14-2 to generate 20 chimeric viruses and evaluated their replication capability in cell culture and their pathogenic potential in mice. Our findings revealed the following: (i) The single envelope (E) protein of SA14-14-2, which contains nine mutations (eight in the ectodomain and one in the stem region), is both necessary and sufficient to render SA14 non-neuroinvasive and non-neurovirulent. (ii) Conversely, the E protein of SA14 alone is necessary for SA14-14-2 to become highly neurovirulent, but it is not sufficient to make it highly neuroinvasive. (iii) The limited neuroinvasiveness of an SA14-14-2 derivative that contains the E gene of SA14 significantly increases (approaching that of the wild-type strain) when two viral nonstructural proteins are replaced by their counterparts from SA14: (a) NS1/1', which has four mutations on the external surface of the core β-ladder domain; and (b) NS2A, which has two mutations in the N-terminal region, including two non-transmembrane α-helices. In line with their roles in viral pathogenicity, the E, NS1/1', and NS2A genes all contribute to the enhanced spread of the virus in cell culture. Collectively, our data reveal for the first time that the E protein of JEV has a dual function: It is the master regulator of viral neurovirulence and also the primary initiator of viral neuroinvasion. After the initial E-mediated neuroinvasion, the NS1/1' and NS2A proteins act as secondary promoters, further amplifying viral neuroinvasiveness.